Endoscopic endonasal transclival approach to the ventral brainstem: Radiologic, anatomic feasibility and nuances, surgical limitations and future directions. (March 2020) - Karadag, Ali; Senoglu, Mehmet; Middlebrooks, Erik H.; Kinali, Burak; Guvencer, Mustafa; Icke, Cigdem; Sayhan, Salih; Karabay, Nuri; Camlar, Mahmut; Olomu, Osarenoma U.; Tanriover, Necmettin
Highlights: This study assesses the relationship between morphology of the sphenoid sinus and the importance of the accurate surgical options. To emphasized that the EETA is effective approach for the potentially exposed critical structures. To emphasized that the limitations of endoscopic surgery will likely decrease with surgical experience and improved anatomic knowledge. Abstract: The endoscopic endonasal transclival approach (EETA) is less invasive than traditional open approaches; however, there is currently limited data on the pre-operative features that may predict success of the EETA. Surgical landmarks and exposure of the EETA and expanded EETA are assessed. We retrospectively measured multiple anatomic features in 154 adult dry skulls, 22 C1 and C2 dry bone vertebrae, and 500 paranasal sinus computed tomography (CT) scans. We also dissected 13 formalin-fixed, silicone-injected adult cadaveric heads. Relevant qualitative and quantitative data were obtained with CT (n = 10) and cadaveric dissection (n = 13). They are expressed as mean (SD), as appropriate and compared with unpaired t tests. Categorical variables were compared with χ 2 tests. We determined the prevalence of clival and sphenoid sinus anatomic variations and assessed potential exposure of the craniovertebral region, based on the relative position of the nasal bone tip, posterior point of the hard palate, and their relation to the position of C1 and C2. Depending on anatomic features, EETA should allow visualization of the ventral brainstem. The mean (SD) dimensions of the surgical window for EETA were 43.2 (5.1) × 18.3 (1.1) mm, in the craniocaudad and horizontal dimensions, respectively. The craniocaudad dimension enlarged to 60.2 (4.7) mm with expanded EETA. The EETA allowed satisfactory exposure for odontoid and C1 anterior arch resection (expanded EETA) in all specimens, regardless of the orientation of the palate. The combination of preoperative radiographic assessment and intraoperative considerations allows safe and effective application and facilitate selection of the most appropriate approach.